Strategi Pemasaran Menyambut Pranatan Baru Pariwisata Yogyakarta (Studi Kasus Hotel Cabin Sutomo) - Sugiyah Sugiyah; Kartika Yuliantari; Nurhidayati Nurhidayati; Dwiyatmoko Puji Widodo (Widya Cipta - Jurnal Sekretari dan Manajemen, 2021)
Tourism, especially hotels, is one sector that has felt the impact of the COVID-19 pandemic. To accelerate the economic recovery of the tourism sector, especially hotels, regulations are needed that can strengthen this change, both from regulations from the central and regional governments that can encourage hospitality to return to enthusiasm referring to health protocols. The purpose of this study is to examine the marketing strategy of the Cabin Sutomo hotel based on the new Yogyakarta tourism institutions. This research is descriptive qualitative, which is based on scientific studies, principles, and fundamental assumptions of science, by utilizing deductive reasoning supported by valid information and then processed for analysis through research principles. The collection method uses interviews and documentation. The results of the study explain the existence of Pergub Number 48 of 2020, the D.I. Government. Yogyakarta regarding Guidelines for Preparation, Guidelines for Implementation of Public Service Activities and Community Economics in the Special Region of Yogyakarta in the prevention and control of Covid-19 and the book Pranatan Anyar Plesiran Jogya, Guidelines for Adapting New Habits of Tourism DIY, encourage Hotel Cabin Sutomo to make changes to marketing strategies, through product aspects services and employees who pay attention to health protocols, prices with new normal jargon, increasing online (digital) promotions. With this measure in 2020 during the pandemic, room sales decreased by 22.7% compared to 2019. With this decline in sales, Hotel Cabin can still operate without reducing employees.Keywords: Marketing strategy, New institutions, Tourism